Implementation of a Wireless system for the processing and comparison of cerebral waves of patients with Amyotrophic Lateral Sclerosis through matlab identifying their basic needs - Meneses Claudio, Brian (2017)
At present diverse illnesses exist between soft, mortal and silent, in which some studies of the biomedical try to minimize and/or help to fight these illnesses. Due to this, in this paper presents a processing and comparison system of brainwaves, the patients with Amyotrophic Lateral Sclerosis, they are not able to move and/or use any of their body extremities so could communicate their basics needs by the brainwaves produced by their brains, taking apart the communication by the flickers, showing a more reliable and exact alternative. The following work consists of the design of a Wireless System able to show the brainwaves produced by the patient with Amyotrophic Lateral Sclerosis and also process and compare to get the meaning of each of them identifying the basics needs; moreover, it will benefit the family because it's going to exist a nonverbal communication with the patient.